1997
DOI: 10.1366/0003702971940701
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional FT-IR Spectroscopy: A Powerful Method to Study the Secondary Structure of Proteins Using H-D Exchange

Abstract: Two-dimensional infrared spectroscopy has been used for the first time to study the conformation of proteins by hydrogen–deuterium exchange. In order to generate the two-dimensional synchronous and asynchronous maps, hydrogen–deuterium exchange of the amide protons of proteins deposited on attenuated total reflection crystals has been used as an external perturbation. Owing to the fact that the amide protons associated with each conformation are not exchanged at the same rate, the different conformational cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
100
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(102 citation statements)
references
References 7 publications
2
100
0
Order By: Relevance
“…Although the synchronous spectrum is always required for interpretation, the asynchronous spectrum is of particular interest, because it permits the distinction of spectral intensity changes that occur out-of-phase (that is, delayed or accelerated), as a function of the applied perturbation (in our case, temperature). Similar 2D plots were used previously to illustrate the chain of events in the dissociation of amide hydrogen bonds in Nmethylacetamide (13), to improve the resolution of individual band components in the spectrum of myoglobin (14), to resolve the temperature-dependent spectra of helix-forming peptides (15), and to detect sudden changes in the hydration of ovalbumin that precede the unfolding of the protein (16). Very recently, Hochstrasser et al (17) reported a different form of 2D (nonlinear) IR spectroscopy in which perturbations to the system are introduced by ultrafast IR laser pulses, allowing the detection of ultrafast vibrational relaxation times in small model peptides, an approach more akin to 2D NMR.…”
mentioning
confidence: 95%
“…Although the synchronous spectrum is always required for interpretation, the asynchronous spectrum is of particular interest, because it permits the distinction of spectral intensity changes that occur out-of-phase (that is, delayed or accelerated), as a function of the applied perturbation (in our case, temperature). Similar 2D plots were used previously to illustrate the chain of events in the dissociation of amide hydrogen bonds in Nmethylacetamide (13), to improve the resolution of individual band components in the spectrum of myoglobin (14), to resolve the temperature-dependent spectra of helix-forming peptides (15), and to detect sudden changes in the hydration of ovalbumin that precede the unfolding of the protein (16). Very recently, Hochstrasser et al (17) reported a different form of 2D (nonlinear) IR spectroscopy in which perturbations to the system are introduced by ultrafast IR laser pulses, allowing the detection of ultrafast vibrational relaxation times in small model peptides, an approach more akin to 2D NMR.…”
mentioning
confidence: 95%
“…Among many applications to proteins, 2D-COS has allowed the investigation of correlations between amide I, amide II, or amide III bands, 10,11 or between bands in the mid-and near-ir regions. [12][13][14] It has also been applied to the analysis of the kinetics of the hydrogen/deuterium exchange of the amide groups in order to obtain information relative to the flexibility and solvent accessibility of the protein secondary structures.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] It has also been applied to the analysis of the kinetics of the hydrogen/deuterium exchange of the amide groups in order to obtain information relative to the flexibility and solvent accessibility of the protein secondary structures. 10,11 Finally, it has extensively been used to get insights into the sequence of events occurring during protein denaturation induced by temperature, 15-18 pressure, 19 or pH. 20 Most studies using 2D-COS have interpreted the asynchronous maps in terms of hierarchical orders of events.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical deformation, 1 -3,7,8,13 -15,18,22,26,27 electrical field, 16,19,21,31,32 and chemical reactions 20,30,39 are representative examples of stimuli that may yield spectral changes that we describe as producing secondary effects as a consequence of the perturbation. For example, the dynamic deformation induces time-dependent spectral changes useful for 2D correlation spectroscopy.…”
Section: External Perturbationmentioning
confidence: 99%
“…A simple, but elegant, example of such a study is an H to D exchange reaction to probe the secondary structure of a protein. 30 …”
Section: External Perturbationmentioning
confidence: 99%